Who deserves to die : constructing the executable subject - Sarat, Austin; Shoemaker, Karl (Book collections on Project MUSE., 2011)
Death penalty scholars "assess the forms of legal subjectivity and legal community that are supported and constructed by the doctrines and practices of punishment by death in the United States. They help us understand what we do and who we become when we decide who is fit for execution."--Back cover.